OBSERVED AND HYPOTHETICAL EFFECT OVER TIME OF THE TERRACED FOREST PLANTATION ON SOIL AND WATER LOSSES AT DOI ANGKHANG HIGHLAND PROJECT, CHIANG MAI - Tangtham, Nipon (วารสารวนศาสตร์ไทย, 2022)
Change of soil and water losses over time of 6 exotic - species from Taiwan namely: Aleurites montana, Zalkova formosana, Liquidambar formosana, Acacia confusa, Fraxinus griffithic, and Paolonia taiwaniana plated on 2 x 2.5 m spacing with narrow bench terrace at Doi Angkhang Highland Project, Fang District, Chiang Mai, was observed using runoff plots of 4 x 15 m installed for each species. Storm runoff and sediment were monitored in 1983, 1984 and 1988 when plantation was 2, 3 and 7-year old respectively. Observed data of soil and water losses from each plot were plotted and hypothetical function were derived for representing the effect of plantation age and terracing on soil and water losses. Result showed that although only 3 different period observation were employed to draw hypothetical trends. All hypothetical and prediction equations seem to logically explain the cause and effect of plantation ages and narrow terracing on soil and water losses of northern highland areas.